Intercultural Communication Anxiety, Intercultural Sensitivity, and Global Awareness in Japan, China and the United States: The Mediating Roles of Culture and Language Competence - Lina, Wang; Wu Xiaoyan; Lee S. Peter; Jiro Takai (Intercultural Communication Studies, 1970)
Intercultural Communication Anxiety, Intercultural Sensitivity, and Global Awareness in Japan, China and the United States: The Mediating Roles of Culture and Language Competence